Performance Management System in Industry: A Systematic Literature Review - Marbun, Tonggo; Sobandi, A.; Risali, Ridho Pangestu Adhitio (International Journal of Science and Society, 2024)
The increasingly competitive business environment necessitates the development of an effective Performance Management System (PMS). According to academics, current research on PMS has not yet reached a consensus on the actual consequences of PMS and the inconclusive results are due to inadequate understanding of the antecedents and effectiveness of PMS. Therefore, this research aims to observe the dimensions commonly used to measure PMS in the industrial context, understand the characteristics of studies, and identify antecedents, outcomes, mediations, and moderations in the literature on PMS in the industrial context over the past 7 years using a systematic literature review with the PRISMA guideline. The scholarly articles in this SLR are those included in the Scopus database from 2018 to 2024. The review results reveal that the dimensions currently used to study PMS originate from dimensions built by previous researchers, namely PMS Accuracy. The majority of the included studies on PMS in this research were published in 2018 and 2021, with most employing quantitative methods and the majority being located in India and Italy. Our research also reveals that PMS has a positive impact at both individual and organizational levels. This SLR contributes to explaining the current research conditions of PMS in the industrial context and also provides suggestions for future PMS research.